Village economies and the structure of extended family networks - Manuela Angelucci; Giacomo De Giorgi; Marcos A. Rangel; Imran Rasul (Institute for the Study of Labor (IZA), 2009)
This paper documents how the structure of extended family networks in rural Mexico relates to the poverty and inequality of the village of residence. Using the Hispanic naming convention, we construct within-village extended family networks in 504 poor rural villages. Family networks are larger (both in the number of members and as a share of the village population) and out-migration is lower the poorer and the less unequal the village of residence. Our results are consistent with the extended family being a source of informal insurance to its members.
urn:nbn:de:101:1-20091104921
Keywords: J12; O12; O17; 330; Extended family network; migration; village inequality; village marginality; Familiensoziologie; Soziales Netzwerk; Soziale Ungleichheit; Ländliche Armut; Mexiko